Analisis Efektivitas Pengolahan Fisik-Biologis Pada Pengolahan Limbah Cair Covid-19 Di Rumah Sakit X - Leonardus L. Leko; Oktavina G. Lp Manulangga; Madalena Da Costa (Journal on Education, 2023)
Liquid waste generated from hospital activities since the Covid-19 pandemic has increased in quantity and contains microorganisms, especially the Corona virus, toxic substances, blood, body fluids sourced from Covid-19 isolation patient activities, treatment rooms, laboratory rooms, equipment and linen washing rooms. Hospital X is one of the Type C Hospitals in Kupang City that handles Covid-19 patients with liquid waste sources originating from the Emergency Room, Hospitalization, Operating Room, ICU Room, Laboratory, Radiology Room, Pharmacy Room, Kitchen, Office, and Laundry. To treat liquid waste generated from each unit, Hospital X uses a Wastewater Treatment Plant (WWTP) with a physical and biological treatment process and uses a closed piping system with gravity flow and pumping. Based on the results of the examination of physical parameters (temperature and pH), chemical parameters (BOD5, COD, TSS, NH3 Total, Oil and Fat, and MBAS), and microbiological parameters (Total coliform) have met the environmental quality standards in accordance with Permen LHK 68/2016 and Permen LHK 05/2014. The liquid waste treatment process at Hospital X is in accordance with the Decree of the Minister of Health of the Republic of Indonesia Number: 1204 / MENKES / SK / X / 2004, namely the hospital has carried out its own liquid waste treatment using a Waste Water Treatment Plant (WWTP).